2001
DOI: 10.1038/35057149
|View full text |Cite
|
Sign up to set email alerts
|

A map of human genome sequence variation containing 1.42 million single nucleotide polymorphisms

Abstract: We describe a map of 1.42 million single nucleotide polymorphisms (SNPs) distributed throughout the human genome, providing an average density on available sequence of one SNP every 1.9 kilobases. These SNPs were primarily discovered by two projects: The SNP Consortium and the analysis of clone overlaps by the International Human Genome Sequencing Consortium. The map integrates all publicly available SNPs with described genes and other genomic features. We estimate that 60,000 SNPs fall within exon (coding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
408
2
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,575 publications
(433 citation statements)
references
References 42 publications
9
408
2
14
Order By: Relevance
“…- mutation rate: According to different studies Homo sapiens , as a species, has a mutation rate around 1.5 × 10 -8 per base pair per generation (bp/gen for short) [10]. However, this value could change along the genome.…”
Section: Introductionmentioning
confidence: 99%
“…- mutation rate: According to different studies Homo sapiens , as a species, has a mutation rate around 1.5 × 10 -8 per base pair per generation (bp/gen for short) [10]. However, this value could change along the genome.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs are generally abundant, but their density differs considerably between different regions of a genome between genotypes in any species, and more so between species. For instance, Sachidanandam et al (2001) [49] reported that the average density of SNPs in the human genome was estimated at about 1 in 1000 bp but is considerably larger in some genomic areas such as the noncoding human leukocyte antigen (HLA) regions [50]. In plant species analysed so far, approximately one SNP was usually present per 200 to 500 bp with large differences between different plant species.…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%
“…Over 99.9% of genome sequences are the same in all humans [1,2] , yet individuals show great distinction from each other.…”
Section: Transcriptome Profilingmentioning
confidence: 99%